Old And New Oral Anticoagulants In Management Of Atrial Fibrillation: A Double-Edged Sword For Women - Basili, Stefania; Raparelli, Valeria; Proietti, Marco; Napoleone, Laura; Ferroni, Patrizia; Franconi, Flavia (Current Vascular Pharmacology, 2015)
Atrial fibrillation (AF), one of the most prevalent supra-ventricular arrhythmia in adults, is related to a substantial increase in the risk of thromboembolic events requiring tailored preventive strategy. In AF, antithrombotic therapy should be individualized according to a careful decisionmaking process, taking in account the likely concomitant presence of risk factors for stroke and bleeding. Anticoagulation management is particularly challenging in women with AF, to the extent that female sex is incorporated in commonly used stratification schemes for both thromboembolic and bleeding risk evaluation. Nevertheless, gender- based differences on the efficacy and safety of either “old” (i.e. vitamin K antagonist) or “new” oral anticoagulants (i.e. direct thrombin inhibitors and activated factor X inhibitors) are not conclusive and not always reported. This review aims to analyse the literature on sex differences in AF anticoagulation management. We focus on safety data, bleeding complications and specific haemostatic mechanisms currently under investigation, which could account for observed disparities among sexes. Moreover, details on sex difference in response to anticoagulant treatment will be discussed. Comparing old and new antithrombotics, a need clearly emerges for differentiated and integrated strategies for the treatment of AF in female patients.
Keywords: Atrial fibrillation